Pelayanan dan Inovasi Perpustakaan Universitas Pamulang Di Masa Pandemi COVID-19 - Maulida Rachma Herliani (UIN Sumatera Utara, 2022)
In this current condition of distance learning, college student are not advised to visit the public libraries or university libraries. However, as we know, that information are always be needed and cannot be delayed. As one of the institutions that prioritizes services to satisfy the user, library must do an innovation to always give the best services during this pandemic. This research aims to study the activities of services and innovation during this pandemic Covid-19 that provided at university libraries. The location of this research was conducted at Pamulang University Library. The research method used is qualitative descriptive method, with data analysis techniques carried out by interviews, obsevation, and literature study. Based on the result of this research, it is known that during the pandemic, the central library of the Central Library of Pamulang University implemented various policies related to its service. Among them are operational hours end constructive visits, face-to-face services that are only permitted for borrowing books, correspondence, and submitting theses. In addition, Pamulang University Library has deficiencies in providing services during a pandemic, one of which is the incomplete collection. This innovation carried out by taking advantage of the opportunities available, namely by promoing and reactivating the digital library that developed by Pamulang University. Keywords: Library, College Library, Library Services, Library Innovation, Pandemic Covid-19